2002
DOI: 10.1007/s00127-002-0555-6
|View full text |Cite
|
Sign up to set email alerts
|

An empirical comparison of substance and alcohol dependence patterns in the homeless in Madrid (Spain) and Los Angeles (CA, USA)

Abstract: The pattern of results is discussed in the light of the differences in both socioeconomic and cultural among Madrid and Los Angeles which might explain, in turn, differences in the homelessness situation as well as in the alcohol and other drug use patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Consistent with the literature (4)(5)(6)(7)(8), this study found that participants experiencing homelessness during the six months before study enrollment had more severe alcohol, medical, employment, legal, and psychiatric problems than participants with housing. Consistent with the literature (4)(5)(6)(7)(8), this study found that participants experiencing homelessness during the six months before study enrollment had more severe alcohol, medical, employment, legal, and psychiatric problems than participants with housing.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the literature (4)(5)(6)(7)(8), this study found that participants experiencing homelessness during the six months before study enrollment had more severe alcohol, medical, employment, legal, and psychiatric problems than participants with housing. Consistent with the literature (4)(5)(6)(7)(8), this study found that participants experiencing homelessness during the six months before study enrollment had more severe alcohol, medical, employment, legal, and psychiatric problems than participants with housing.…”
Section: Discussionsupporting
confidence: 88%
“…High rates of stimulant and alcohol dependence evidenced by participants reflect known substance use patterns among MSM and substance dependence patterns among homeless populations in Los Angeles County [24,25]. The high rates of depression, ASPD and PTSD observed in the sample suggest both causes and/or consequences of experiencing homelessness in a major metropolitan area of the US.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of alcohol dependence in homeless populations is generally high and can be as high as 86 % [22]. Very high (73 %) lifetime prevalence rates (defi ned as the percentage of individuals who report having been diagnosed with the disorder in their lifetime, regardless of current diagnostic status) were reported by Fichter & Quadfl ieg [23] in male homeless adults in Munich; lower rates have been found elsewhere -Madrid 28 % [24], Paris 25 % [25]. In Los Angeles, alcoholism was detected in 60 % of homeless men.…”
Section: Discussionmentioning
confidence: 99%